G401(P) Low vitamin d levels in children with ataxia-telangiectasia. (24th May 2017) - Prayle, AP; Bush, A; Suri, M; Bhatt, J
Abstract : Aims: Ataxia telangiectasia (A-T; birth incidence 1/300, 000) is characterised by progressive neurological features, increased sensitivity to radiation and malignancy risk, and progressive respiratory failure. Most children are wheelchair users in the teenage years. Low Vitamin D is important in many immune pathways, is a key factor in osteomalacia, and is implicated in the pathogenesis of multiple respiratory disorders. Vitamin D deficiency occurs due to low intake or poor sunlight exposure. Children with A-T show high rates of malnutrition despite nutritional support, and may avoid sunlight due to malignancy risk. We assessed the vitamin D levels of a cohort of children with A-T. Methods: 25-Hydroxy-Vitamin D (25OH-VitD) has been measured routinely since May 2015 in our clinic. We use the RCPCH position statement definitions of deficient 25OH-VitD as less than 25 nmol/L, sub-optimal as 25 to less than 50 nmol/L and normal as 50 nmol/L and over. To examine the impact of nutritional status on 25OH-VitD, we calculated the weight Z score for each of these categories, and we compared the proportion wasted (Z score < 2), and a 3-sample test for equality of proportions (prop.test in R 3.3). Results: Measurements were made in 46 children (see table). We restricted our analysis to the first measurement for each patient. 28 were female. 12 (26%) measurements of 25OH-VitD were in the deficient range, 22 (48%) were suboptimal and 12 (26%) were normal. There was no clear impact of wasting (weight Z score < 2) on vitamin D (p=0.4). Conclusion: Vitamin D deficiency was extremely common in this cohort of patients. The lack of a clear association of low vitamin D with weight Z score suggests that factors other than malnutrition for example lack of sun exposure may be a factor. We have instituted a programme of screening and supplementation of vitamin D. Together with immobility, Vitamin D deficiency increases the risk of osteoporosis in A-T.